INHIBISI DNMT3B UNTUK MENGHAMBAT PERKEMBANGAN SEL KANKER KULIT DENGAN SENYAWA MINYAK ATSIRI KAYU MANIS MELALUI STUDI IN SILICO DAN PROTEOMIK - Khusnul Agustina; Putri Anggraini Budianto; Christopher Filando Santoso; Rumiyati Rumiyati (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2022)
Introduction: Cinnamon (Cinnamomum cassia) is often used as a medicinal plant because of its antioxidant properties. UV overexposure leads to many harmful impacts, one of them being the increasement rate of skin cancer risk. UV rays increase DNMT3B expression and ROS level. However, anti-skin cancer drugs that target DNMT3B have not been explored yet, and this study aims to explore cinnamon essential oil's potency in targeting DNMT3B to stop UV-induced skin cancer development. Methods: The research was carried out through an in silico and proteomic approach. Research materials were obtained from various databases including CMAUP, ChEMBL, PubChem, Google Scholar, PubMed, and RCSB. The materials that have been obtained are processed using KNIME and MOE V.2010 software Result: As a result, KNIME analysis showed many similarities between four of cinnamon's active compounds and DNMT3B inhibitors (azacytidine and decitabine). Three of the essential oil compounds; Cinnamaldehyde, cis-2-methoxy cinnamic acid, and coumarin are predicted to inhibit DNMT3B. Moreover, using the molecular docking approach, cis-2-methoxy cinnamic acid has more stable bonds compared to its native ligand (glycerol). Conclusion: In conclusion, the active compounds in cinnamon essential oil were potential to inhibit DNMT3B and prevent skin cancer development with cis-2-methoxy cinnamic acid as the most potent inhibitory compound. Keywords: Cinnamon, skin cancer, DNMT3B, cis-2-methoxycinnamic acid.